STRATEGY FOR PROVIDING CARGO TRANSPORTATION SERVICES TO THE POPULATION (Marketing Journal, 2025)
The article provides a scientific analysis of the strategy for providing freight transportation services to the population by road transport in the Republic of Uzbekistan, its structural components, and development directions. Key tasks such as increasing the volume of freight transportation, modernizing infrastructure, digitalization, and the use of environmentally friendly transport are identified. Based on statistical data and the example of a local transport company, existing problems, trends, and strat egic proposals are developed. The research results demonstrate the opportunities for enhancing economic efficiency through the optimization of the freight transportation system.
Keywords: Uzbekistan – 2030; transport; freight transportation; infrastructure; ecology; green transport. 286